2001
DOI: 10.1063/1.1376147
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between electroresistance and magnetoresistance in La0.82Ca0.18MnO3 single crystal

Abstract: The resistivity of La0.82Ca0.18MnO3 single crystal has been investigated as a function of external magnetic field and separately under an applied current flow. The measurements were carried out at various temperatures below and above the ferromagnetic transition temperature TC. It has been found that the dynamic electroresistance exhibits stunning similarities to the colossal magnetoresistance at the corresponding temperatures. The correlation observed between the electric- and magnetic-field effects is attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…It has been shown that electric current and/or electric field has strong influence on manganites. [5][6][7][8][9][10][11][12][13][14] Most previous work are on the manganites with charge ordered state. Very recently, Gao et al.…”
mentioning
confidence: 99%
“…It has been shown that electric current and/or electric field has strong influence on manganites. [5][6][7][8][9][10][11][12][13][14] Most previous work are on the manganites with charge ordered state. Very recently, Gao et al.…”
mentioning
confidence: 99%
“…To our knowledge, ER or the lack of it has not been reported previously in a sample of this composition. = 0.2 At x = 0.18, just below the x-value of the sample to be next discussed, one report has been shown a closely-correlated ER and MR [43], with the ER being attributed to an electrically-induced MR, and another report an effectively decoupled ER and MR [8]. This x = 0.18 material, as it is cooled, first enters a FMM phase (below about 170 K), then a FMI phase (below about 120 K) [8,44].…”
Section: =mentioning
confidence: 99%
“…2,3) However, an unsolved issue is whether the origin of both the effects is same or different. In single crystals of doped manganites [2][3][4][5][6] argued that the boundary between the two segregated phases -ferromagnetic metallic (FMM) and charge-ordered insulating (COI) -moves under electric field establishing connectivity among the FMM islands. This, in turn, gives rise to charge carrier type (p or n) dependent ER yet no shift in transition temperature (T MI ).…”
Section: Introductionmentioning
confidence: 99%